Answers

2016-01-23T17:00:09+05:30
Just put the values of x as ⅔ and find a as 1st equation. Then put x = -3 and you will get another equation with a and b. By Substitution Method, put value of a in 2nd equation. You'll get b. Put value of b in 1st equation to get a.
0
2016-01-23T17:19:01+05:30
In the equation Ax^2+Bx+C=0,,product of the roots equal to C/A ,,sum of roots equal to B/A...so in ax^2+7x+b=0 sum of roots equal to 7/a=2/3+[-3] so here we get 'a' value,,then come product of roots b/a=2/3*[-3]=-2,,here sub a value as -3 from above solution,,,we get b value as 6
0